2021
DOI: 10.1111/anu.13275
|View full text |Cite
|
Sign up to set email alerts
|

Dietary carbohydrate‐to‐lipid ratios modulate juvenile hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatus ): Effects on growth, serum biochemistry, intestinal digestion and hepatic metabolism of glucose and lipid

Abstract: The hybrid grouper (♀Epinephelus fuscoguttatus × ♂ E. lanceolatus) is a carnivorous species that has been widely cultured in China. It has many heteroses, such as fast growth rate, delicious taste, rich nu-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 93 publications
6
5
0
Order By: Relevance
“…The experimental groupers were divided into three feeding mode groups as follows: continuous feeding group (8 weeks, C group), prolonged starvation group (8 weeks, S group) and refeeding after starvation group (starving for 4 weeks + refeeding for 4 weeks, R Group). As the shared control group specifically, the C group is consistent with M group in article reported by Chen et al (2021).…”
Section: Methodssupporting
confidence: 87%
See 2 more Smart Citations
“…The experimental groupers were divided into three feeding mode groups as follows: continuous feeding group (8 weeks, C group), prolonged starvation group (8 weeks, S group) and refeeding after starvation group (starving for 4 weeks + refeeding for 4 weeks, R Group). As the shared control group specifically, the C group is consistent with M group in article reported by Chen et al (2021).…”
Section: Methodssupporting
confidence: 87%
“… As the shared control group specifically, the trial diet formulation in this study is consistent with diet M in article reported by Chen et al (2021). …”
Section: Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…Our results showed that fish fed CHO:L ratio of 1.92 achieved the best growth performance compared to fish fed CHO:L ratios of 0.91 and 3.91. Previous studies on groupers [ 18 , 29 ] have also shown that the best growth was achieved at medium CHO:L ratio, which was similar to our results. A significant increase in WG and SGR and a significant decrease in FCR were observed with carbohydrase supplementation at a CHO:L ratio of 3.91, indicating that carbohydrase act as a growth promoter.…”
Section: Discussionsupporting
confidence: 93%
“…In order to maximize profits, diets are often formulated to contain high levels of CHO:L ratio to reduce feed costs. Although the optimal glycolipid ratio requirements at the juvenile stage of grouper have been studied [ 18 , 19 , 20 ], there is little research on the addition of carbohydrase based on different glycolipid ratios. With this in mind, the purpose of this study was to assess the influence of carbohydrase supplementation on growth performance, carbohydrate metabolic enzyme and glut2 gene expression in the Hybrid Grouper-fed diets with different CHO:L ratios.…”
Section: Introductionmentioning
confidence: 99%